We share the sun : the incredible journey of Kenya's legendary running coach Patrick Sang and the fastest runners on earth - Gearhart, Sarah (Pegasus Books, 2023)
"In We Share the Sun, Sarah Gearhart takes us inside this high-octane world of elites of which few are even aware of and even fewer have ever seen. We are immersed in Sang's remarkable story, from his college days in the US to winning an Olympic medal in the steeplechase, and his journey to become a man who redefines what coaching means"--